The role of water-energy nexus in optimising water supply systems – Review of techniques and approaches. (February 2018) - Vakilifard, Negar; Anda, Martin; A. Bahri, Parisa; Ho, Goen
Abstract: Considering water-energy nexus in optimising water supply systems not only ensures the sustainability of the water supply for increasing water demand but also diminishes water-related energy and environmental concerns. This paper presents a review highlighting knowledge gaps in optimisation models related to the water-energy nexus in water supply systems or "water supply side of the nexus". Studies reported in the literature are categorised and systematically analysed in terms of different energy sources, centralised/ decentralised approaches and system parameters uncertainties. Several major gaps are identified. These include the lack of optimisation models capturing spatial aspects as well as environmental impacts of the nexus problems. The shortage of models considering uncertainties associated with water demand and renewable energy supply is another knowledge gap in this area. However, the main gap is the absence of models for optimising long-term planning of water supply system considering renewable energy within an urban context. Accordingly, based on this review, we have suggested pointers for future studies in the water supply side of the nexus.